2014
DOI: 10.1017/s0029665114001426
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota, the pharmabiotics they produce and host health

Abstract: A healthy gut microbiota plays many crucial functions in the host, being involved in the correct development and functioning of the immune system, assisting in the digestion of certain foods and in the production of health-beneficial bioactive metabolites or ‘pharmabiotics’. These include bioactive lipids (including SCFA and conjugated linoleic acid) antimicrobials and exopolysaccharides in addition to nutrients, including vitamins B and K. Alterations in the composition of the gut microbiota and reductions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 186 publications
(228 reference statements)
1
87
0
5
Order By: Relevance
“…Tyramine also causes the release of norepinephrine from sympathetic nerves, reversing re-uptake through the norepinephrine transporter and has been demonstrated to induce serotonin (5-HT) production by enterochromaffin cells [64]. Given that intestinal 5-HT [65] and catecholamines [66] have been proposed as mediators of microbe-gut-brain signalling via modulation of the enteric nervous system, the impact of luminal tyramine levels on the gut-brain axis may warrant further investigation. The current study focused on faecal metabolites, with the understanding that gut lumen metabolites acting at the level of the gut epithelium, enteroendocrine cells, and enteric nervous system may play a role in microbe-gut-brain signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Tyramine also causes the release of norepinephrine from sympathetic nerves, reversing re-uptake through the norepinephrine transporter and has been demonstrated to induce serotonin (5-HT) production by enterochromaffin cells [64]. Given that intestinal 5-HT [65] and catecholamines [66] have been proposed as mediators of microbe-gut-brain signalling via modulation of the enteric nervous system, the impact of luminal tyramine levels on the gut-brain axis may warrant further investigation. The current study focused on faecal metabolites, with the understanding that gut lumen metabolites acting at the level of the gut epithelium, enteroendocrine cells, and enteric nervous system may play a role in microbe-gut-brain signalling.…”
Section: Discussionmentioning
confidence: 99%
“…One obvious limitation of our current study is that we did not examine these isolates for their ability to secrete catecholamines and serotonin, which are important neurotransmitters. However, recent studies by others have clearly shown the presence and importance of these metabolites from gut-associated microbes, including the bidirectional character of microbiota–host interactivity via neuromediators including BAs [37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Bioactive EPA, docosapentaenoic acid and DHA can partly inhibit a number of aspects of inflammation including leukocyte chemotaxis, adhesion molecule expression and leukocyte–endothelial adhesive interactions, production of n-6 PUFA derived eicosanoids from arachidonic acid, production of inflammatory cytokines and T-helper 1 lymphocyte reactivity, extensively reviewed34. Thus, interactions between resident gut microbes and dietary derived fatty acids with implications for health have been described353637.…”
mentioning
confidence: 99%